Advancement of a modular rotor permanent magnet flux switching machine for high torque performance - Soomro, Irfan Ali (2021)
Usage of electric motors in electric vehicle applications have gained a lot of attention since the motor must possessed high torque density and power. Permanent magnet flux switching machines have attracted considerable interests in recent years since the flux focusing is utilizable, both armature windings and PM excitation sources are on the stator, and the salient pole rotor is simple yet robust. Regrettably, salient rotor and stator of PMFSM with single tooth winding have inherited flux cancellation, flux leakage, high iron losses, high winding losses, and longer flux paths which reduced the torque and efficiency of the motor. In this thesis, a flux switching motor using permanent magnet employing modular rotor is designed and investigated for high torque making it suitable for high torque performances applications. The design engaged a three-phase 12 stator tooth taking up four sets of windings per phase with 10 pole feasible modular rotor. The characteristics performance of modular rotor PMFSM were designed and analysed using JMAG designer 14.1 utilizing 2D finite element analysis (2D-FEA). The initial 12S/10P modular rotor PMFSM topology achieved an average torque of 34.44 Nm with an output power of 5.67 kW. To further improve the performance of modular rotor PMFSM, local optimization approach was conducted which achieved an average torque of 60.49Nm and an output power of 23.34 kW while maintaining the same motor’s outer diameter. Furthermore, to compare modular rotor PMFSM with salient rotor PMFSM, FEFSM and HEFSM were utilized to choose best candidate for high torque performance. In comparison, optimized modular rotor PMFSM generated the highest output torque followed by optimized salient rotor HEFSM which generated the second highest torque. Consequently, the modular rotor PMFSM produced higher average torque, less iron losses, less weight and shorten flux path than using salient rotor pole PMFSM, FEFSM or HEFSM. In conclusion, modular rotor PMFSM confirms good agreement with high torque applications.